The complete chloroplast genome sequence of Docynia indica (Wall.) Decne - Dawei Wang; Chen Shi; Hongyan Tang; Chengzhong He; Anan Duan; Hede Gong (Mitochondrial DNA. Part B. Resources, 2019)
Docynia indica (Wall.) Decne. (Duo-Yi) is a high economic value for exploitation and utilization wild fruit tree species with edible and medicinal values in southwest China. We have sequenced the chloroplast genome to facilitate genetic improvement of this species and to assess phylogenetic relationships among major lineages. The result showed that the total chloroplast genome size of Duo-Yi was 159,546 bp in length, containing a pair of inverted repeats (IRs) of 26,369 bp, which were separated by a large single copy (LSC) and small single copy (SSC) of 87,650 bp and 19,158 bp, respectively. The overall guanine-cytosine (GC) content of the chloroplast genome was 36.6%. There were 125 genes in the chloroplast genome, which including 82 protein-coding genes, 35 transfer RNA genes, and 8 ribosomal RNA genes. Among these genes, there were 14 genes with one intron and 3 genes have two introns. The result of phylogenetic analysis indicated that the Duo-Yi was closely related to the genera of Malus doumeri.